Ironi Krisis Kasih Dalam Komunitas Pengikut Kristus Masa Kini - Djone Georges Nicolas; Tirza Manaroinsong; Lasino J.W. Putro; Lastri Hutagalung; Yustisia Siregar (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to find out the causes of the crisis of love found in the community of Christ's followers today. Nowadays, it is found that the lives of most of the believers who in fact profess to be followers of Christ, but in fact show the value of life that is contrary to their confession of faith, whereas Christianity is identical with love and care based on a high impulse of compassion towards others as a form of service. The real. Because, if the basis of Christianity is no longer love as has been taught and demonstrated by Jesus Christ during his presence and ministry on earth, of course it is an irony. The research approach method used is descriptive qualitative with data collection through various sources such as the Bible and other literature, interviews, and other sources that are related to the topic of study. The result: first, the purpose of life for some followers of Christ is not to exalt Christ, but rather for their own sake. Second, the value of the life that some followers of Christ live is not different from the value of the life of people in the world (outside of Christianity).